TYPES OF INTEGRATION IN THE EDUCATIONAL PROCESS - Lazzat Saidaliyeva; Jursinay Uzokova; Janar Juzjasarova (Journal Park Publishing, 2023)
The integration course is one of the educational subjects, which is studied to deepen and increase interdisciplinary knowledge (integrative knowledge), and to form it. It is created on the basis of various types, methods, styles, objects of interdisciplinary integration.
Keywords: Integration, interactive, skills, knowledge, modern, evolution.